Comparing cardiac rehabilitation programmes for people with coronary heart disease. (2nd October 2021) - Harrison, Joanna; Edwards, Catherine; Hill, James
Abstract : Secondary prevention of adverse cardiovascular events is a major focus in the care of patients with coronary heart disease. Cardiac rehabilitation aims to address patient risk factors through lifestyle modifications, such as increased physical activity and dietary modification. This commentary evaluates and critically appraises a network meta-analysis of cardiac rehabilitation programmes, including exercise and non-exercise approaches, for patients with coronary heart disease.